Two sets of dynamic stretching of the lower body musculature improves linear repeated-sprint performance in team-sports - Asmadi Ishak (Tanjong Malim, 2019)
Two sets of dynamic stretching of the lower body musculature improves linear repeated-sprint performance in team-sports by Asmadi Ishak